2009
DOI: 10.1080/13803390903042379
|View full text |Cite
|
Sign up to set email alerts
|

Attention and working memory deficits in mild cognitive impairment

Abstract: Mild cognitive impairment (MCI) has emerged as a classification for a prodromal phase of cognitive decline preceding the emergence of Alzheimer's disease (AD). We examined neuropsychological functioning in a sample of 60 adults with amnestic-MCI (a-MCI), 32 with subjective complaints of memory impairment (subjective-MCI, s-MCI), 14 with mild AD, and 25 age-matched controls. Both the a-MCI and s-MCI groups displayed impaired attentional processing, working memory capacity, and semantic language, with a-MCI disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
135
4
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(154 citation statements)
references
References 31 publications
(41 reference statements)
6
135
4
9
Order By: Relevance
“…Prior research confirms that CANTAB tests effectively discriminate between normal functioning individuals and various clinical populations including mild cognitive impairment (Saunders & Summers, 2010),…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research confirms that CANTAB tests effectively discriminate between normal functioning individuals and various clinical populations including mild cognitive impairment (Saunders & Summers, 2010),…”
Section: Discussionmentioning
confidence: 99%
“…Tests can be run individually or in a customisable battery to enable users to test a series of participants on a set sequence of tests (Cambridge Cognition Ltd, 2012). The CANTAB has been utilised extensively in the study of various populations, including those with schizophrenia (Levaux et al, 2007), Parkinson's disease (Foltynie, Brayne, Robbins, & Barker, 2004), Huntington's disease , frontal and temporal lobe excisions (Owen, Roberts, Polkey, Sahakian, & Robbins, 1991) and normal functioning adults (De Luca, Wood, Anderson, & Buchanan, 2003;Robbins et al, 1998) The construct validity of CANTAB has been largely based upon the ability of test measures to discriminate between normal adults and various clinical populations, including mild cognitive impairment (Klekociuk, Summers, Vickers, & Summers, 2014;Saunders & Summers, 2010), Alzheimer's disease (Saunders & Summers, 2010), epilepsy (Torgersen, Johan, Hans, Bernt, & Arne, 2012), ADHD (Gau & Shang, 2010) and various central nervous system diseases (Roque, Teixeira, Zachi, & Ventura, 2011). Despite its widespread application and ability to discriminate between clinical and normal functioning groups, the association between established neuropsychological measures and CANTAB components remains under-researched.…”
Section: Introductionmentioning
confidence: 99%
“…We first employed an object recognition test to elucidate short-term non-spatial working memory (26). Working memory is one of the types of short-term memory that have been reported to be impaired at an early stage in patients with AD (27). In the sample trial of this test, no significant difference in total time spent exploring two identical objects was observed between sham and OBX groups, indicating virtually no differences in the ability to recognize objects between animals.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focused on these factors for the following reasons: First, previous reports from this laboratory and others (9,18,27) demonstrated that OBX deteriorates the septo-hippocampal cholinergic system and thereby induces learning and memory performance deficits. Secondly, cholinergic systems affect glutamate receptor function via the activation of muscarinic receptors coupled with Gq/11-PKC signaling systems and thereby modulate glutamatergic neurotransmission (9,35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Le GrC devrait démontrer une performance sur les variables de MdT supérieure au GrE. Assurément, il a été cité plus haut qu'en présence d'une ACL (GrE), la MdT serait une des premières structures cognitives atteintes (Missonnier et al, 2006;Saunders & Summers 2009). L'analyse des résultats permet de constater que les scores aux tâches de MdT du GrE sont tous plus faibles que les scores obtenus par le GrC, mais seulement trois variables ont démontré une différence statistiquement significative entre les deux groupes, soit l'indice de MdT du MEM-III, séquence de lettes-chiffres et le score z de la série la plus longue au test de séquence de chiffres en ordre indirect.…”
Section: Deuxième Hypothèseunclassified